Factors Associated with Pneumonia in Children Under Five after Earthquake: A Path Analysis Evidence from West Nusa Tenggara, Indonesia - Nur Isniani Ningsih; Harsono Salimo; Setyo Sri Rahardjo (Journal of Epidemiology and Public Health, 2019)
Background: Pneumonia is an infectious disease which is the main killer among children under five. This study aims to analyze socio-economic and environmental determinants of the incidence of pneumonia in children under five after the earthquake.Subjects and Method: This study used observational analytic using case control. The total sample of 237 children under five aged 12-59 months old and the sampling technique was fixed disease sampling. The independent variables in this study were birth weight, exclusive breastfeeding, nutritional status, immunization status, maternal education, family income, healthy behavior, physical quality of the house, exposure to cooking fuel smoke, smoking activities of family members and active village influences. Collecting the variables was through questionnaires and analyzed by using path analysis.Results: Birth weight